2020
DOI: 10.1007/s10620-020-06369-1
|View full text |Cite
|
Sign up to set email alerts
|

Low Rates of Advance Care Planning (ACP) Discussions Despite Readiness to Engage in ACP Among Liver Transplant Candidates

Abstract: Background: Patients with end-stage liver disease (ESLD) awaiting liver transplantation (LT) are seriously ill and experience fluctuating periods of clinical decompensation. Discussion of a patient's advance care planning (ACP) wishes early in their dynamic disease course is critical to providing value-aligned care while awaiting LT. We aimed to evaluate current ACP documentation and assess readiness to engage in ACP in this population. Methods:We conducted a retrospective study of adults undergoing LT evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 22 publications
1
21
0
Order By: Relevance
“…In addition, they wanted to avoid end-of-life decision-making conflicts. This is consistent with the research findings of Wang et al 30 However, not all elderly AIDS patients considered it necessary to have an ACP discussion at this stage. This was a result of their misunderstanding of the ACP concept and lack of AIDS knowledge.…”
Section: Strengthen Public Education To Promote the Acp Cognitionsupporting
confidence: 91%
“…In addition, they wanted to avoid end-of-life decision-making conflicts. This is consistent with the research findings of Wang et al 30 However, not all elderly AIDS patients considered it necessary to have an ACP discussion at this stage. This was a result of their misunderstanding of the ACP concept and lack of AIDS knowledge.…”
Section: Strengthen Public Education To Promote the Acp Cognitionsupporting
confidence: 91%
“…This low frequency of performing ACP is not unique to our institution. 17,18 Nationally, less than 50% of older adults have any form of an AD, and rates of ACP may be even lower for patients undergoing surgery. 4,5 Our results are consistent with the existing literature by demonstrating low rates of adherence with multiple aspects of ACP.…”
Section: Discussionmentioning
confidence: 99%
“…Advance care planning (ACP) with patients on the LT waiting list One qualitative (34), two quantitative (21, 35) and one quasi-experimental (29) study contributed to the theme of ACP with patients on the LT waiting list (Table 4). These studies highlighted that although patients report that they are ready to engage in the process of ACP (34,35), there is little evidence of this taking place with one study showing that 9% of these patients reported completing an ACP prior to their LT evaluation, and only 10% reporting having a Durable Power of Attorney written in their medical notes (35). Patient participants remember receiving information about the risk of death whilst they were on the LT waiting list but were not aware of receiving information about making a decision about a Goals of Care Designation i.e.…”
Section: Study Participantsmentioning
confidence: 99%